Intertextual and intersonic resonance in Richard de Fournival’s Bestiaire d'amour: combining perspectives from literary studies and musicology - Leach, EE; Morton, J (Librairie Droz, 2018)
The Bestiaire d'amour, as its somewhat strange title suggests, is a multiply hybrid textual beast. The bulk of the text comprises a list of animals whose behaviours it allegorizes: in this way, its title seems aptly to situate it within the bestiary tradition. A closer look, though, reveals that in contrast to the theological and moralizing allegories found in bestiaries, this text interprets all the animals to refer to different kinds of male and female lovers. Its initial appearance as a bestiary is deceptive and its plot, in which a desperate first-person male narrator despairs of his ability to persuade his female addressee to reciprocate his love, belongs to the conventions of lyric poetry—the amour of the title. Yet the Bestiaire itself is not strictly lyrical. Indeed, not only is it in prose, but this fact is self-consciously discussed by the narrator, who claims to have lost his ability to compose and to sing love-lyrics and who is sending a prose letter—a contreescrit —as a last-ditch attempt to win the lady who has so far resisted his advances. Eliza Zingesser notes it as a « kind of palinode to the narrator’s earlier lyric writings », which Sarah Kay called a « désenchantement » (both a pessimistic disenchantment and an « un-singing ») that is nonetheless « saturated with song ». This saturation is precisely the concern of the present article and we will further tease out Kay’s insight that the Bestiaire d’amour is preoccupied with the nature of vocal production as a means of communication that is troublingly shared between irrational animals and rational humans.